Effect of fish oil on neutrophil chemiluminescence induced by different stimuli in patients with rheumatoid arthritis. - Magarò, M (1992)
Lipid composition plays an important part in the structural and metabolic functions of cell membranes. In particular the production of inflammatory mediators such as prostaglandins and leukotrienes is dependent on polyunsaturated fatty acid precursors. Neutrophil leucocytes participate in inflammatory processes by their phagocytic and killing activities which can be monitored by measuring the photon emission (chemiluminescence). Chemiluminescence was measured in a luminol dependent system after stimulation by either particulate (zymosan) or soluble (phorbol myristate acetate) stimulus in a group of 10 patients with rheumatoid arthritis before and 21 and 45 days after treatment with a diet supplemented with eicosapentaenoic and docosahexaenoic acids. Ten patients with rheumatoid arthritis continuing their usual diet were used as control subjects. A progressive reduction of chemiluminescence stimulated by zymosan and phorbol myristate acetate was found in the patients treated with fish oil supplementation. This result correlated well with the reduction in erythrocyte sedimentation rate and an improvement of clinical parameters. The effects of fish oil derived lipids on neutrophil chemiluminescence are probably due to a change of the lipid composition of the cell membrane which is dependent on the esterification of eicosapentaenoic acid and docosahexaenoic acid in cellular membrane phospholipids. The modification of membrane lipid composition seems to interact in a non-specific way with the metabolic activation of neutrophils during phagocytosis.